TEKNIK PENILAIAN HASIL BELAJAR SISWA BERDASARKAN KURIKULUM 2013 DALAM MATA PELAJARAN SENI BUDAYA DI SMP NEGERI 1 PADANG - Pratama, Eki; Yuliasma, Yuliasma; Sudarman, Yos (SENDRATASIK UNP, 2019)
AbstractÂ The article aims to describe the implementation of learning outcomes assessment techniques, constraints faced by teachers in the implementation of studentsâ€™ learning outcomes assessment techniques and solutions to the obstacles faced by arts and culture teachers on learning outcomes assessment based on the 2013 curriculum in art and culture subjects. This research was a qualitative research with descriptive methods. The types of data used were primary and secondary data. Data collection techniques were conducted by interview, observation, and documentation. In this research, the technique used was source triangulation. The steps to analyze data were data reduction, data presentation and drawing conclusions. In general, the results confirmed that the art and culture teachers at SMP Negeri 1 Padang had not yet implemented as well as applied the assessment of learning outcomes based on the 2013 curriculum. The problems encountered were 1) the teachers had difficulty when observing outside the classroom, 2) the students who were not in accordance with the competencies achievements, 3) limited time to conduct all attitude assessment techniques. The solutions to these constraints are 1) the teachers use the time effectively, 2) The teachers motivate the students to be more active in learning arts and culture, 3) The teachers provide actual examples in delivering the material, 4) The teachers report to the principal about lack of facilities and infrastructures, 5) Teachers and schools try to provide direction, seminars and upgrading about learning based on the 2013 Curriculum. Keywords: student learning outcomes assessment techniques, 2013 curriculumÂ